2017
DOI: 10.1016/j.nutres.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Review of the mechanisms of probiotic actions in the prevention of colorectal cancer

Abstract: The purpose of this review is to discuss the potential mechanisms of probiotics action in colorectal cancer prevention. In this regard, the composition of the intestinal microbiota is considered as an important risk factor in the development of colorectal cancer, and probiotics are able to positively modulate the composition of this microbiota. Studies have shown that the regular consumption of probiotics could prevent the development of colorectal cancer. In this respect, in vitro and experimental studies sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(91 citation statements)
references
References 77 publications
0
87
0
4
Order By: Relevance
“…It has been reported that SCFAs are able to induce epigenetic changes, arrest cell cycle, and increase the expression of pro‐apoptotic genes (Dos Reis et al., ). The promoting effect of probiotics on apoptosis may be through SCFA production, immunomodulation, and increased expression of genes and proteins involved in regulation of apoptosis pathway (Dos Reis et al., ). Consumption of L. acidophilus suppressed the growth of tumor and enhanced the apoptosis of tumor cells in an animal model of segmental orthotopic colon cancer, in which mice were implanted with CT‐26 murine colon adenocarcinoma cells (Chen et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that SCFAs are able to induce epigenetic changes, arrest cell cycle, and increase the expression of pro‐apoptotic genes (Dos Reis et al., ). The promoting effect of probiotics on apoptosis may be through SCFA production, immunomodulation, and increased expression of genes and proteins involved in regulation of apoptosis pathway (Dos Reis et al., ). Consumption of L. acidophilus suppressed the growth of tumor and enhanced the apoptosis of tumor cells in an animal model of segmental orthotopic colon cancer, in which mice were implanted with CT‐26 murine colon adenocarcinoma cells (Chen et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of GBR and L. acidophilus may be the most effective synbiotics in facilitating apoptosis.The effect of GBR on apoptosis induction may be associated with SCFAs produced from GBR by certain colonic bacteria as observed in prebiotic-involved studies. It has been reported that SCFAs are able to induce epigenetic changes, arrest cell cycle, and increase the expression of pro-apoptotic genes (DosReis et al, 2017). The promoting effect of probiotics on apoptosis may be through SCFA production, immunomodulation, and increased expression of genes and proteins involved in regulation of apoptosis pathway(Dos Reis et al, 2017).…”
mentioning
confidence: 99%
“…Gamallat et al 33 observaram que os probióticos possuem uma atividade de quimioprevenção e um possível efeito protetor no desenvolvimento e progressão da carcinogênese do cólon. Essa atividade anticarcinogênica atribuída aos probióticos é descrita pela modificação da composição e alterações na atividade metabólica da microbiota intestinal, pela ligação e degradação de compostos carcinogênicos presentes no lúmen intestinal e pela produção de compostos com atividade anticarcinogênica, como os AGCCs e o ácido linoleico conjugado, além da imunomodulação, melhora da barreira intestinal, inibição da proliferação de células cancerosas e indução da apoptose 34 . 21 , o uso de pre, pro e/ou simbióticos no pré-operatório não parece apresentar efeitos benéficos.…”
Section: Discussionunclassified
“…Recent reports have clearly demonstrated that Fusobacterium (F.) nucleatum is one of the major risk factors for colorectal cancer [40][41][42] . Some studies suggested that F. nucleatum showed immunosuppressive activities of T cell response in the tumor microenvironment.…”
Section: Colorectal Cancermentioning
confidence: 99%